A Novel Microwave Sensor for Real‐Time Online Monitoring of Roll Compacts of Pharmaceutical Powders Online—A Comparative Case Study with NIR. Issue 5 (9th March 2015) - Gupta, Anshu; Austin, John; Davis, Sierra; Harris, Michael; Reklaitis, Gintaras
<x xml:space="preserve">Abstract</x> Control of particulate processes is hard to achieve because of the ease with which powders tend to segregate. Thus, proper sensing methods must be employed to ensure content uniformity during operation. The role of sensing schemes becomes even more critical while operating the process continuously as measurements are essential for implementation of feedback control (Austin et al. 2013. J Pharm Sci 102(6):1895–1904; Austin et al. 2014. Anal Chim Acta 819:82–93). A microwave sensor was developed and shown to be effective in online measurement of active pharmaceutical ingredient (API) concentration in a powder blend. During powder transport and hopper storage before processing, powder blends may segregate and cause quality deviations in the subsequent tableting operation. Therefore, it is critical to know the API concentration in the ribbons as the content uniformity is fixed once the ribbon is processed. In this study, a novel microwave sensor was developed that could provide measurement of a roller compacted ribbon's API concentration online, along with its density and moisture content. The results indicate that this microwave sensor is capable of increased accuracy compared with a commercially available near‐IR probe for the determination of content uniformity and density in roller compacted ribbons online. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:1787–1794, 2015